Factibilidad para la creación de una empresa de elaboración y comercialización de ropa deportiva ubicada en el cantón Machala, provincia El Oro, año 2014 - Basurto García, Tania Estefanía (2015)
The problems that exist in companies sportswear clothing in the city of Machala are increasing for this reason is to define the problem variables studied conducting the formulation thereof and justifying the reason the project will pose a hypothesis the same as that discussed for determining if satisfied. The theoretical foundation is established with the basic terms of reference for the project. Besides the basic mode is set, the type of research, techniques and tools for collecting and processing data. Market research is done by determining the universe and sample size, analysis and interpretation of the results obtained through surveys, technical and financial study, which is one of the most important parts for the development and implementation developed project, allowing determine whether the investment is feasible or not. After completing the study of the project come to establish the respective conclusions and recommendations thereof based on the results obtained. The present project realized, besides being viable and profitable, is a new source of wealth and employment; thus contributing to decline in part the unemployment rate and generate economic benefits to the partners